Reconceptualizing Legal Arrangement on the Doctor-Patient Relationship in Indonesia - Iswandari, Hargianti Dini; Hoque, Sanjana (LAW REFORM, 2022)
The doctor-patient relationship in Indonesia has changed. In the past, patients were inferior to doctors, but over time the relationship has put the two in a more balanced position. This article aims to examine the legal substance in regulating doctor-patient relationships in Indonesia. The arguments presented in this study demonstrated the increase in the number of civil lawsuits or complaints/criminal lawsuits has a substantial impact on legal resolution shifting. Although the law placed the legal relationship among two parties as mere contract-civil relationship, the criminalization is increasingly favored in recent years. As a recommendation, future law-making process needs to comprehensively consider medical science as the basis to lay the legal foundation in regulating doctor-patient relationships.